COMMUNITY ENGAGEMENT FOR CULTURAL LANDSCAPES: A CASE STUDY OF HERITAGE PRESERVATION AND TOURISM DEVELOPMENT - Esposito De Vita, Gabriella; Ragozino, Stefania; Simeone, Maurizio (BDC. Bollettino Del Centro Calza Bini, 2015)
In order to discuss partnership models and action protocols to be implemented in regeneration processes for enhancing the relationships slow tourism-cultural landscapes-urban regeneration, a case study approach has been chosen. The paper focuses on a purposely-selected experience in Naples (Italy): the Marine Protected Area of La Gaiola. In this distinguished example of waterfront area, a group of activists is developing an integrated system of initiatives for protecting cultural and environmental resources by promoting compatible uses for education and tourism purposes. The case study has been developed by interacting with the local stakeholders involved in social, environmental and economic activities in order to address the topic of developing effective partnerships for sustaining successful regeneration processes according to the needs of promoting cultural tourism and intelligence in tourism. Keywords: cultural landscapes, urban regeneration, civic activation